1997
DOI: 10.1111/j.1600-0528.1997.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of oral hygiene self‐efficacy and outcome expectancy questionnaires

Abstract: In order to measure social cognitive constructs in the oral hygiene domain, questionnaires containing self-efficacy and outcome expectation items were developed. Items were generated to measure personal beliefs in brushing and flossing ability under a variety of circumstances, and expected outcomes from performing oral hygiene behaviors that might be positive, negative, primary and secondary. In the first study, factor scales were developed on the basis of the responses from 90 subjects awaiting dental treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 25 publications
7
71
0
4
Order By: Relevance
“…Previously, dental self-efficacy has been found to relate to oral hygiene practices and dental visiting (McCaul et al 1985, Tedesco et al 1994, Stewart et al 1997) and, correspondingly, diabetes self-efficacy to diabetes self-care (Hurley & Shea 1992, Littlefield et al 1992, Kavanagh et al 1993. The results of the present study are accordant with these findings concerning health behavior and, furthermore, the relation found here between diabetes self-efficacy and metabolic balance is parallel to that reported by Kavanagh et al (1993) and Day et al (1996).…”
Section: Self-efficacysupporting
confidence: 82%
See 2 more Smart Citations
“…Previously, dental self-efficacy has been found to relate to oral hygiene practices and dental visiting (McCaul et al 1985, Tedesco et al 1994, Stewart et al 1997) and, correspondingly, diabetes self-efficacy to diabetes self-care (Hurley & Shea 1992, Littlefield et al 1992, Kavanagh et al 1993. The results of the present study are accordant with these findings concerning health behavior and, furthermore, the relation found here between diabetes self-efficacy and metabolic balance is parallel to that reported by Kavanagh et al (1993) and Day et al (1996).…”
Section: Self-efficacysupporting
confidence: 82%
“…Self-efficacy concerning tooth brushing and flossing have been found to associate with the frequencies of tooth brushing, flossing and dental visiting (Stewart et al 1997), but self-efficacy has not been found to associate with the oral hygiene status (Wolfe et al 1991). Dental health education has been shown to improve dental self-efficacy .…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…La prác-tica se consideró aceptable en 91,5 % de padres/cuidadores; 6,4 % buena y 2,1 % mala. A=Asistencia del adulto al odontólogo, B=Asistencia del niño/a al odontólogo, C=Higiene oral en el niño/a, D=Crema dental para la higiene oral del niño/a, E=Alimentación con lactancia materna, biberón, complementaria, F=Mecanismos para calmar la inquietud/ansiedad del niño/a o para acostarlo DISCUSIÓN En salud oral se han utilizado instrumentos de medición de conocimientos, actitudes y prácticas para acercarse al entendimiento de la realidad cotidiana (12)(13). En Colombia, un ejemplo es la encuesta de representaciones sociales del Estudio Nacional de Salud Bucal III (ENSAB-III) de 1999 (14), que incluye creencias, conocimientos y prácticas de madres de 18 a 69 años, respecto a la salud bucal de los niños.…”
Section: Métodosunclassified
“…La encuesta de conocimientos, actitudes y prácticas inicialmente elaborada (6) contaba con una fuerte base teórica (7); sin embargo, mostraba fallas en su construcción y aplicación, que no permitían una interpretación real de datos y su extrapolación (12).…”
Section: Métodosunclassified